Roundtable In EFL Argumentative Writing: Effects on Achievement and Perceptions - Rohmana Rohmana; Sitti Agustina; Waode Ade Sarasmita Uke; Anugrah Puspita Ayu Muhammad; Nurul Atma; Yustih Yasin; Wa Ode Sitti Wardani; Minerva A. Chavez (FKIP Universitas Lampung, 2026)
This study examined how the Roundtable technique, combined with process writing, affected EFL students' argumentative writing performance and their perceptions of its use in a Critical Writing course. A mixed-methods explanatory sequential design was used. A 42-item questionnaire, pre-test and post-test writing scores, and semi-structured interviews were used to collect quantitative and qualitative data from 32 undergraduate students in the English Education Department of Universitas Halu Oleo. Descriptive statistics and a paired-samples t-test were used to assess the quantitative data. In contrast, thematic analysis of the qualitative data was used to supplement and clarify the quantitative results. After the intervention, students' achievement in argumentative writing significantly improved, according to the findings. With a statistically significant difference (t(31) = 41.97, p < .001), the mean score rose from 71.63 on the pre-test to 81.00 on the post-test, indicating a very large effect. With an overall mean of 3.12 on a four-point Likert scale and strong internal consistency (Cronbach's alpha = .91), the questionnaire findings likewise indicated generally positive opinions of the instructional paradigm. These findings were corroborated by the interview data, which demonstrated that Roundtable promoted classroom participation, idea development, argument organization, critical engagement, and revision. However, problems remained, especially in vocabulary, grammar, coherence, and evidence-based reasoning. The results reveal the pedagogical effectiveness of combining the Roundtable and process writing to improve students’ argumentative writing skills and to create dynamic classroom settings in EFL higher education. It is recommended that further research explore the effect of the Roundtable on specific features of argumentative writing, including coherence, evidence integration, and linguistic accuracy, using a quasi-experimental design with larger, more diverse samples. Keywords: cooperative learning, EFL argumentative writing, mixed-methods study, process writing, Roundtable, student perceptions, writing achievement.